Analisis Pengaruh Citra Destinasi, Kualitas Perjalanan Terhadap Minat Berprilaku Wisatawan Di Kepulauan Seribu Dki Jakarta Sebagai Destinasi Prioritas Indonesia - Gantina, Devita; Lintangkawuryan, Yulia (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2018)
The development of tourism is increasingly interesting to study, given that many domestic and foreign tourists travel. Plus, the tourism sector is being promoted by the government. In 2016 the government established 10 priority tourism destinations as